THE INFLUENCE OF LEARNING DISCIPLINE AND LEARNING MOTIVATION ON SELF-REGULATED LEARNING WITH PARENTING PATTERNS AS A MODERATING VARIABLE - Putri Andini; Etty Gurendrawati; Ati Sumiati (International Journal of Multidisciplinary Research and Literature, 2023)
This research is motivated by internal factors such as learning discipline and learning motivation also external factors such as parenting patterns that can influence self-regulated learning. This study aims to determine the influence of learning discipline on self-regulated learning, the influence of learning motivation on self-regulated learning, the influence of learning discipline on self-regulated learning with parenting patterns as a moderating variable and the influence of learning motivation on self-regulated learning with parenting patterns as a moderating variable. This type of research is a quantitative research with a survey method. The affordable population used was 143 students with a sample of 105 students. The results of this study indicate that there is an influence of learning discipline on self-regulated learning